2017
DOI: 10.1037/drm0000044
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of need for cognition, field independence and locus of control on the incidence of lucid dreams during a 12-week induction study.

Abstract: This article reports an investigation of two proposed theories, the predispositional and experiential, regarding the association of personality variables to lucid dreaming incidence during a 12-week lucid dreaming induction programme. The study found no differences between those who did and did not report lucid dreams during the programme on baseline measures of Field Independence, Locus of Control or Need for Cognition. There was an observed significant change towards a Field Independent orientation between b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…This is close to the success rate reported in the NALDIS of 17.4%. These findings replicate the NALDIS and several other studies that have shown the MILD technique to be effective ( LaBerge, 1988 ; Levitan, 1989 , 1990a , 1990b , 1991 ; Edelstein and LaBerge, 1992 ; Levitan et al, 1992 ; LaBerge et al, 1994 , 2018 ; Levitan and LaBerge, 1994 ; Saunders et al, 2017 ; Konkoly and Burke, 2019 ). Although there were no statistically significant differences between the effectiveness of the hybrid SSILD/MILD technique and the other techniques in Cohort 2, results show that the overall lucid dreaming rate in Week 2, the improvement in week 2 compared to Week 1, and the effect size were all lowest for the SSILD/MILD hybrid group.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is close to the success rate reported in the NALDIS of 17.4%. These findings replicate the NALDIS and several other studies that have shown the MILD technique to be effective ( LaBerge, 1988 ; Levitan, 1989 , 1990a , 1990b , 1991 ; Edelstein and LaBerge, 1992 ; Levitan et al, 1992 ; LaBerge et al, 1994 , 2018 ; Levitan and LaBerge, 1994 ; Saunders et al, 2017 ; Konkoly and Burke, 2019 ). Although there were no statistically significant differences between the effectiveness of the hybrid SSILD/MILD technique and the other techniques in Cohort 2, results show that the overall lucid dreaming rate in Week 2, the improvement in week 2 compared to Week 1, and the effect size were all lowest for the SSILD/MILD hybrid group.…”
Section: Discussionsupporting
confidence: 87%
“…However, the authors did not provide statistics to indicate how effective this training program was except that 39 lucid dreams were reported. Saunders et al (2017) found that a greater proportion of participants who practiced several techniques over a 12-week period (including RT, MILD and WBTB) experienced lucid dreaming compared to a control group (45 vs. 6%). However, the frequency of lucid dreaming is unclear.…”
Section: Introductionmentioning
confidence: 92%
“…Furthermore, scholars should continue attempting to identify whether patterns of discontinuity and continuity are consistent or varied across individuals. For instance, some existing work has identified benefits of a labile sleep–wake pattern in terms of the number of cycles through sleep stages upon knowledge awareness tasks ( 84 , 85 ) and recent work has identified that lucid dreaming training benefits performance in field independence tasks ( 86 ). As such identifying patterns of cognitive functioning and discontinuity of consciousness that seem optimal for both mental health and memory consolidation could pave the way for similar training or intervention studies, if patterns of discontinuity may be changeable across individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that reported the significant association between internal locus of control and lucid dreaming were based on the retrospective incidence of lucid dreams (Blagrove & Hartnell, 2000;Blagrove & Tucker, 1994;Patrick & Durndell, 2004). A recent study (Saunders, Clegg, Roe, & Smith, 2017), which experimentally induced lucid dreams in participants, did not find a difference between the baseline and postinduction scores in locus of control. This seems to suggest that the significant association observed by the previous researchers is more characteristic of a trait than of a state.…”
mentioning
confidence: 92%